Endoscopic assessment of oesophagitis: clinical and functional correlates and further validation of the Los Angeles classification. Issue 2 (1st August 1999) - Lundell, L R; Dent, J; Bennett, J R; Blum, A L; Armstrong, D; Galmiche, J P; Johnson, F; Hongo, M; Richter, J E; Spechler, S J; Tytgat, G N J; Wallin, L
Abstract : BACKGROUND: Endoscopic oesophageal changes are diagnostically helpful and identify patients exposed to the risk of disease chronicity. However, there is a serious lack of agreement about how to describe and classify the appearance of reflux oesophagitis AIMS: To examine the reliability of criteria that describe the circumferential extent of mucosal breaks and to evaluate the functional and clinical correlates of patients with reflux disease whose oesophagitis was graded according to the Los Angeles system. METHODS: Forty six endoscopists from different countries used a detailed worksheet to evaluate endoscopic video recordings from 22 patients with the full range of severity of reflux oesophagitis. In separate studies, Los Angeles system gradings were correlated with 24 hour oesophageal pH monitoring (178 patients), and with clinical trials of omeprazole treatment (277 patients). RESULTS: Evaluation of circumferential extent of oesophagitis by the criterion of whether mucosal breaks extended between the tops of mucosal folds, gave acceptable agreement (mean κ value 0.4) among observers. This approach is used in the Los Angeles system. An alternative approach of grouping the circumferential extent of mucosal breaks as occupying 0–25%, 26–50%, 51–75%, 76–99%, or 100% of the oesophageal circumference, gave unacceptably high interobserver variation (mean κ values 0–0.15) for all but the lowest category of extent (mean κ value 0.4). Severity of oesophageal acid exposure was significantly (p<0.001) related to the severity grade of oesophagitis. Preteatment oesophagitis grades A–C were related to heartburn severity (p<0.01), outcomes of omeprazole (10 mg daily) treatment (p<0.01), and the risk for symptom relapse off therapy over six months (p<0.05). CONCLUSIONS: Results add further support to previous studies for the clinical utility of the Los Angeles system for endoscopic grading of oesophagitis.